Host Specificity and Spatial Distribution Preference of Three Pseudomonas Isolates - Tovi, Nesli; Frenk, Sammy; Hadar, Yitzhak; Minz, Dror (Frontiers in Microbiology, 2019)
Plant hosts recruit and maintain a distinct root-associated microbiota based on host and bacterium traits. However, past studies disregarded microbial strain-host specificity and spatial micro-heterogeneity of the root compartment. Using genetic manipulation, confocal laser scanning microscopy, real-time quantitative PCR and genome sequencing we characterized the colonization patterns of three Pseudomonas spp. isolates native to wheat roots, on the micro-scale. Namely, isolates P. fluorescens NT0133, P. stutzeri NT124 and P. stutzeri NT128. All three isolates preferentially colonized wheat over cucumber roots that served as control for host specificity. Furthermore, not only had the isolates strong host specificity but each isolate had a distinct spatial distribution on the root, all within a few millimeters. Isolate P. stutzeri-NT0124 preferentially colonized root tips, whereas P. fluorescens-NT0133 showed a preference for zones distant from the tip. In contrast, isolate P. stutzeri-NT0128 had no preference for a specific niche on the root. While all isolates maintained genetic potential for motility and biofilm formation their phenotype varied significantly and corresponded to their niche preference. These results demonstrate the importance of spatial colonization patterns, governed by both niche and bacterial characteristics which will have great importance in future attempts to manipulate the plant microbiome by constructing synthetic microbial consortia.